A Cross-Platform Mobile Attendance System Utilizing Geofencing and Multi-Factor Authentication - Wisdom Korkortsi; Edmund Dasori Azundow; Ramatu Al-Hassan; Yaw Amankrah Sam-Okyere; Mohammed Izzu-deen Zakariah (Applied Engineering, Innovation, and Technology, 2026)
The challenge of accurately managing student attendance in higher education persists due to the limitations of manual methods, such as susceptibility to fraud and inefficiency amid growing enrollments. This paper introduces a cross-platform mobile attendance system developed using the Flutter framework and Google Firebase backend, incorporating geofencing and device-binding multi-factor authentication to ensure secure, "foolproof" verification. The system operates on a BYOD model, eliminating hardware costs while supporting both Android and iOS devices. A simulation test with 30 students evaluated performance, yielding an average verification time of 8.7 seconds, 98% authentication success rate, and effective fraud prevention against unauthorized devices and out-of-location check-ins. Results highlight the system's robustness, low latency, and adaptability to location errors via dynamic geofencing. This scalable, cost-effective solution addresses gaps in existing systems, including platform exclusivity and privacy concerns from biometrics, making it ideal for Ghanaian universities facing resource constraints and large class sizes.